1997
DOI: 10.1007/s11661-997-0141-3
|View full text |Cite
|
Sign up to set email alerts
|

A study on the subgrain superplasticity of extruded Al-Al3Ni eutectic alloy

Abstract: A directionally solidified Al-Al 3 Ni eutectic alloy was extruded to obtain micron-size subgrains with [111] fiber texture. The extrusion temperature was varied to have different distributions of the Al 3 Ni eutectic particles. Choosing the fiber axis as the loading axis, the tensile test results at 500 ЊC indicate that the elongation is concave downward and strain-rate dependent. Reducing the number of intragranular particles increases the maximum elongation as well as the strain rate of maximum elongation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Choosing the tensile direction paralcles are during this superplastic-like deformation. To clarify lel to the fiber axis and setting the testing temperature at these questions, details of our recent microstructure study 500 ЊC, we have found in our previous studies [6,7] that superwill be reported in the following. plastic-like behavior of extruded Al-Al 3 Ni eutectic alloy can take place if the Al 3 Ni eutectic particles in the as-extruded state are residing only intergranularly (i.e., at the sub-bound-II.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Choosing the tensile direction paralcles are during this superplastic-like deformation. To clarify lel to the fiber axis and setting the testing temperature at these questions, details of our recent microstructure study 500 ЊC, we have found in our previous studies [6,7] that superwill be reported in the following. plastic-like behavior of extruded Al-Al 3 Ni eutectic alloy can take place if the Al 3 Ni eutectic particles in the as-extruded state are residing only intergranularly (i.e., at the sub-bound-II.…”
Section: Introductionmentioning
confidence: 96%
“…However, the final TEM 300 pct has been reported. [4][5][6][7] This total elongation is signifimicrostructure of the test material with superplastic-like cant in superplastic forming since the elongation required behavior reveals that some of the intergranular particles are in related engineering designs rarely exceeds 300 pct. [8] no longer intergranular.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the development and the advance of superconducting magnet technologies, the application of a high magnetic field during the solidification process of metal materials to achieve aligned microstructure has been recognized as one of the useful technologies in materials processing [8][9][10][11] . Al-Ni alloys with non-eutectic compositions normally contain a wide range of volume percent eutectic which can meet higher technical demands on material properties and have been an important branch of research on functionally graded materials processing [12][13][14][15] . Studies on the mechanical properties of fiber-reinforced composite suggested that for Al-Ni alloys with an aligned-Al 3 Ni structure, their tensile and fatigue properties were remarkably improved in the direction along which the Al 3 Ni phases were aligned [16] .…”
mentioning
confidence: 99%